Penerapan Model Pembelajaran Cooperative Tipe Team Assisted Individualization dalam Meningkatkan Hasil Belajar Siswa - Reza Oktaviani; Rita Zahara; Sungging Handoko (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2018)
The title of this research is application of team type cooperative learning models is assisted by individualization in increasing student learning results. The title was taken and motivated by learning outcomes that less on student an analysis learning model that can increase learning results of each student both in cognitive aspect, affective aspect, psychomotor aspech. The purpose of this observation to apply the kearning model in upgrading learning outcomes of the student. This research is quantitative because data of the research have the shape of numbers and the analysis was using statistic. The methode of this study used quasy experimental and by using “nonequivalent control group” group design. In class of experiment and class of control were held pretest and posttest. Data collection technique was using observation, for working and writing test. The research instrument used observation sheets, sheets for working and sheets to test questions. Based on result of statistical test there is research hypothesis which reads there is an increase learning outcome on experiment class by using cooperative type team assisted individualization learning model, so the hypothesis of research is accepted.